2022
DOI: 10.1186/s40694-022-00143-w
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles isolated from dsRNA-sprayed barley plants exhibit no growth inhibition or gene silencing in Fusarium graminearum

Abstract: Numerous reports have shown that incorporating a double-stranded RNA (dsRNA)-expressing transgene into plants or applying dsRNA by spraying it onto their leaves successfully protects them against invading pathogens exploiting the mechanism of RNA interference (RNAi). How dsRNAs or siRNAs are transferred between donor host cells and recipient fungal cells is largely unknown. It is speculated that plant extracellular vesicles (EVs) function as RNA shuttles between plants and their pathogens. Recently, we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…Host-induced gene silencing (HIGS) and spray-induced gene silencing (SIGS) are emerging biotechnological approaches that use double-stranded RNA (dsRNA) to target essential fungal genes and suppress their expression. Several studies have demonstrated that HIGS and SIGS can effectively reduce FHB symptoms and mycotoxin accumulation by targeting genes involved in fungal growth, virulence, and toxin biosynthesis [159,160]. HIGS and SIGS offer several advantages over other control methods, such as specificity, durability, safety, and compatibility with existing breeding programs.…”
Section: Disease Control Based On Virulence Genementioning
confidence: 99%
“…Host-induced gene silencing (HIGS) and spray-induced gene silencing (SIGS) are emerging biotechnological approaches that use double-stranded RNA (dsRNA) to target essential fungal genes and suppress their expression. Several studies have demonstrated that HIGS and SIGS can effectively reduce FHB symptoms and mycotoxin accumulation by targeting genes involved in fungal growth, virulence, and toxin biosynthesis [159,160]. HIGS and SIGS offer several advantages over other control methods, such as specificity, durability, safety, and compatibility with existing breeding programs.…”
Section: Disease Control Based On Virulence Genementioning
confidence: 99%
“…Recently, the group of Aline Koch has suggested that plants EVs may only play a minor or indirect role in the delivery and uptake of host‐induced gene silencing (HIGS)- and spray‐induced gene silencing (SIGS)-associated RNAs. They showed that co-cultivation of Fusarium graminearum ( Fg ) with EVs (P100) isolated from CYP3RNA-expressing A. thaliana plants as well as from CYP3RNA-sprayed barley plants did not have any effect on the expression of CYP51 in Fg ( Schlemmer et al , 2022 ). Interestingly, they had previously shown that >70% of HIGS-derived siRNAs in Arabidopsis were found to be extravesicular ( Schlemmer et al , 2021 ).…”
Section: Potential Functions Of Exrnasmentioning
confidence: 99%
“…Recently, EVs isolated from barley (Hordeum vulgare) plants sprayed with a dsRNA construct that targeted the three F. graminearum CYP51 genes for silencing were found to harbor siRNAs derived from the topically applied RNA [119]. However, when these CYP51 siRNA-containing EVs were used to treat F. graminearum infection, no significant inhibition of the degree of infection or target gene silencing was observed [120].…”
Section: Plant Defense and Cross-kingdom Rnaimentioning
confidence: 99%